Prognostic value of a low post-exercise ankle brachial index as assessed by primary care physicians - Diehm, Curt; Darius, Harald; Pittrow, David; Schwertfeger, Markus; Tepohl, Gerhart; Haberl, Roman L.; Allenberg, Jens-Rainer; Burghaus, Ina; Trampisch, Hans Joachim (Atherosclerosis, 2011)
Objective - We aimed to investigate whether the post-exercise ankle brachial index (ABI) performed by primary care physicians offers useful information for the prediction of death or cardiovascular events, beyond the traditional resting ABI. An additional focus was on patients with intermittent claudication and normal resting ABI. - Methods - Using data from the 5-year follow-up of 6468 elderly patients in the primary care setting in Germany (getABI study) we used multivariate Cox regression models adjusted for age, gender and conventional risk factors to determine the association of resting ABI and/or post-exercise ABI and all-cause mortality/morbidity. - Results - Mean post-exercise ABI in the total cohort was 0.977 and resting ABI was 1.034. For post-exercise ABI, a threshold value of 0.825 had nearly the same sensitivity (28.6%) and specificity (85.7%) as the conventionally used resting ABI with a cut-off value of 0.9 to predict death. Compared to patients with normal post-exercise ABI, a low post-exercise ABI was associated with an almost identical risk increase for mortality (hazard ratio [HR] 1.56, 95% confidence interval [CI] 1.30-1.86) as a low resting ABI (HR 1.65; CI 1.39-1.97) and/or myocardial infarction/stroke. Slight differences were observed for coronary/carotid revascularisation and peripheral revascularisation/amputation. In combined models it could not be shown that post-exercise ABI yielded relevant additional information for the prognosis of mortality and/or myocardial infarction/stroke, not even in the subgroup analysis of patients with intermittent claudication and normal resting ABI. - Conclusions - It could not be shown that the post-exercise ABI is a useful tool for the prognosis of mortality and/or myocardial infarction/stroke beyond the resting ABI.
Available online 27 November 2010
Gesehen am 30.05.2022